La città di Francesc Eiximenis. A proposito del «Dotzè del Crestià», I, 1 - Potestà, Gian Luca (Caplletra. Revista Internacional de Filologia, 2007)
The work «Lo Crestià» by Eiximenis is an encyclopaedic project that develops, among many other subjects, the political worries of his author. The Dotzè is the place where the ideas about the ideal society, a society that takes form in the space of the city, are related. Which exactly the image of the ideal city is and with which sources Eiximenis works, is the central subject of this article. Some of these sources have been fully studied, one of them being, for example, the relationship between the Dotzè with the Politics by Aristotle. This is one of the aspects that places the book within Aristotle’s trend of modernization of political language, a reference point that surpasses an influence until now considered central to political Agustinism.